Fourfold paralogy regions on human HOX-bearing chromosomes: Role of ancient segmental duplications in the evolution of vertebrate genome - Asrar, Zainab; Haq, Farhan; Abbasi, Amir Ali (Molecular phylogenetics and evolution, 2013)
[Display omitted] ► Phylogenetic history of 44 gene families residing on human chromosomes 2/7/12/17. ► Tree topologies were compared to test for consistency in duplication histories. ► Members of 44 families were categorized into four distinct co-duplicated groups. ► Results decisively reject the assumption that HOX-paralogons were shaped by WGDs. ► HOX-paralogons structured by small-scale duplications spread across animal’s history. Susumu Ohno’s idea that modern vertebrates are degenerate polyploids (concept referred as 2R hypothesis) has been the subject of intense debate for past four decades. It was proposed that intra-genomic synteny regions (paralogons) in human genome are remains of ancient polyploidization events that occurred early in the vertebrate history. The quadruplicated paralogon centered on human HOX clusters is taken as evidence that human HOX-bearing chromosomes were structured by two rounds of whole genome duplication (WGD) events. Evolutionary history of human HOX-bearing chromosomes (chromosomes 2/7/12/17) was evaluated by the phylogenetic analysis of multigene families with triplicated or quadruplicated distribution on these chromosomes. Topology comparison approach categorized the members of 44 families into four distinct co-duplicated groups. Distinct gene families belonging to a particular co-duplicated group, exhibit similar evolutionary history and hence have duplicated simultaneously, whereas genes of two distinct co-duplicated groups do not share their evolutionary history and have not duplicated in concert with each other. The recovery of co-duplicated groups suggests that “ancient segmental duplications and rearrangements” is the most rational model of evolutionary events that have generated the triplicated and quadruplicated paralogy regions seen on the human HOX-bearing chromosomes.